2022
DOI: 10.11113/humentech.v1n1.5
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Effectiveness of Aromatherapy Oils in the Learning of Autistic Children in an Educational Setting

Abstract: This review was performed to determine the objective of therapeutic intervention on the learning of autistic children. This literature review aimed at addressing two critical issues: (1) the benefits of aromatherapy oils, including the understanding of its effect on ASD children in literature, and (2) the significance of its effect on their learning. An extensive search was carried out on various online databases, including ERIC, ProQuest Education Journals, and Scopus using the following phrases: (“aromathera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…Moss, et al [9], found that ambiently diffused aromas of rosemary essential oils had a positive effect on children's working memory performance. Also, according to [5] aromatherapy helps memory by harmonizing smell messages, incorporating the aroma of essential oils into the learning environment, or repeating lectures with smells…”
Section: Effects Of Aromatherapy On All Involved In the Learning Jour...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moss, et al [9], found that ambiently diffused aromas of rosemary essential oils had a positive effect on children's working memory performance. Also, according to [5] aromatherapy helps memory by harmonizing smell messages, incorporating the aroma of essential oils into the learning environment, or repeating lectures with smells…”
Section: Effects Of Aromatherapy On All Involved In the Learning Jour...mentioning
confidence: 99%
“…Research within the field of aromatherapy emphasizes investigating the effect of different essential oils on precise brain centers known to regulate an individual's attention level during the teaching process [4]. According to [5] both parents and children reported feelings of calmness when essential oils were sprayed or diffused in the environment, and matching learning concepts with good scents could increase the efficiency of emotional learning in classroom.…”
Section: Introductionmentioning
confidence: 99%